Gastrointestinal stromal tumours: a series of 5 cases with review of literature - Devi, Junu; Phukan, Neeharika (International Journal of Research in Medical Sciences, 2023)
Gastrointestinal stromal tumors (GISTs) are the most common malignant mesenchymal lesions of the gastrointestinal tract originating from the interstitial cells of Cajal. They are characterized by overexpression of the tyrosine kinase receptor, protein product of c‑KIT gene (KIT). In this case series we retrieved from our database, a total number of 5 patients, admitted and operated in the surgical department of Gauhati Medical College and Hospital and histopathologically diagnosed as GIST in the Pathology department of Gauhati Medical College and Hospital. The age range of the patients was 25 to 55 years, with mean age of 43.6 years. Out study population consisted of 2 males and 3 females. Out of 5 cases, 1 occurred in the stomach, 2 in jejunum, 1 in ileum and 1 involved the ileocaecal region; 2 were diagnosed as Malignant GIST and 3 as Benign. The differential diagnoses for spindle cell GISTs are leiomyoma, leiomyosarcoma, intra-abdominal desmoid fibromatosis, schwannoma, inflammatory myo-fibroblastic tumor and solitary fibrous tumor and that for epithelioid GIST include neuroendocrine carcinoma. Knowledge of the differential diagnoses of mesenchymal lesions of the gastrointestinal tract is important to accurately diagnose both GIST and non GISTs as the management approach is very different.